The role of PEG-40-stearate in the production, morphology and stability of microbubbles - Owen, J (University of Oxford, 2018)
This data was created from 2015 to 2018 examining PEG via Fluoresence microscopy, accusizer, DLS, langmuir trough and ultrasound. Excel, Zen and Matlab will be required to open the data.